Correlation between Preoperative Osteitis Degree with Postoperative Endoscopic Score in Chronic Rhinosinusitis - Apriansyah, Apriansyah; Dewi, Anna Mailasari Kusuma; Ningrum, Farah Hendara (RSUP Dr. Kariadi, 2023)
BACKGROUND: In chronic rhinosinusitis patients, there is a subgroup of patients with persistent symptoms after treatment, who often shows bone thickening and remodeling in their paranasal sinuses and described as osteitis. Osteitis can be evaluated by several methods, one of which is the Global Osteitis Score (GOS) AIM: To analyse the correlation between preoperative osteitis degree with the postoperative endoscopic scores in chronic rhinosinusitis METHOD: It was an observational study with cross-sectional design. We use GOS from CT scan before surgery and Lund Mackay’s endoscopic score 4 weeks after Functional Endoscopy Sinus Surgery (FESS). The analysis performed with Spearman correlation test. RESULT: There were 30 patients as subjects. There statistical analysis test between preoperative osteitis degree with post operative endoscopic score showed p = 0.296 with r = 0.197. The analysis result between risk factors for wound healing with the postoperative endoscopic score were allergic rhinitis (p = 1.000), polyps (p = 0.624), and smoking (p = 0.309) CONCLUSION: There is no significant correlation between preoperative osteitis degree with the postoperative endoscopic score, but there is a tendency for a positive correlation between preoperative osteitis degree with the postoperative endoscopic score. There was no significant correlation between allergic rhinitis, polyps, and smoking habits with postoperative endoscopic score